Cost analysis of antimicrobial drugs using a common commercial drug manual: an insight into rational prescribing - Dixit, Alok; Mishra, Ajit Kumar; Adiyodi, Arjun S.; Singh, Chandraveer; Pathak, Asha; Gupta, Vinay (International Journal of Basic & Clinical Pharmacology, 2025)
Background: At present, there are a lot of drug industries that manufacture their own brand for a given drug molecule. A thorough knowledge of cost of different brands of the drug molecule is necessary for doctors so that they can prescribe the affordable drug brand to the patient. This can improve the compliance and therapy outcome. The aim is to analyse the cost variation of drug molecules available in market and their comparison with drugs available in Jan Ausadhi Kendra. Methods: Cross sectional descriptive study, using current index of medical specialities (CIMS) 2023 drug manual, the relevant details of some commonly used anti-microbials were obtained. The cost ratio and the percentage cost variation of different drugs were calculated. Results: The highest cost ratio was for tablet Fluconazole and least for tablet Atazanavir 300 mg. The maximum % cost variation was for tablet Fluconazole and least for Injection Caspofungin. Some of the costly drugs in Janaushadhi store were tablet Norfloxacin-Tinidazole, Moxifloxacin, Cefuroxime, Azithromycin and Piperacillin-Tazobactam injection respectively. Conclusion: Since there is a wide price variation in different brands of a given same anti-microbial agent, the clinicians need to focus on the cheapest drug brands available in the drug market so that they can reduce the cost burden on patients and improve the patient compliance.